The girl on the balcony : Olivia Hussey finds life after Romeo & Juliet - Hussey, Olivia; Martin, Alexander, 1973- (Kensington Books, 2018)
"In 1968, Olivia Hussey became one of the most famous faces in the world, immortalized as the definitive Juliet in Franco Zeffirelli's Romeo & Juliet. Now the iconic girl on the balcony shares the ups and downs of her truly remarkable life and career ... In this candid memoir, Olivia Hussey tells her story: from being an "It Girl" in swinging 60s London and her enduring friendship with Romeo & Juliet co-star Leonard Whiting, through three tumultuous marriages, motherhood, stage-four breast cancer, debilitating agoraphobia, bankruptcy, and ultimately, a journey of self-discovery in India that led her on a path to fulfillment"--Jacket.